SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SUPPLIER TERBAIK PRODUK LAMPU ELEKTRONIK MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Musdalifa Thamrin; Lilis Ariska; Sulistiyawati Nardi (Yayasan Nusantara Hasana Berdikari, 2023)
CV Maju Sentosa is an electronic lighting product company that markets various types of lamps. Currently CV.Maju Sentosa is constrained in choosing the right supplier and there is no decision support system that aims to provide predictions to get the best supplier. In the supplier selection carried out by CV. Maju Sentosa based on price and other criteria. To resolve these obstacles can be done by building a decision support system using the Analytical Hierarchy Process (AHP) method, in which each criterion in the assessment factors of the alternatives will be compared between one another so as to provide a priority value output that produces a system that provides an assessment for each supplier. The results of this study are to be able to build a decision support system using the Analytical Hierarchy Process (AHP) method which provides the best supplier ranking results based on the final value obtained by each supplier starting from the highest value to the lowest value with the supplier selection process so that CV .Maju Sentosa is easy in supplier selection.